(untitled) (Sociologisk Forskning, 2025)
Critical race studies have highlighted race humor as a phenomenon that reinforces normative whiteness. While previous research has examined the pleasurable superiority in laughter elicited by race humor, this article explores other affects and how comedians retrospectively negotiate the meaning of past jokes. The material includes podcasts, TV documentaries, books, and newspaper articles in which comedian Henrik Schyffert reflects on his career and reassesses early jokes that have faced criticism. The aim is to shed light on the affective practices involved in handling past jokes, where humor’s meaning is renegotiated based on what becomes silent or taboo. The analysis demonstrates how affects such as shame, regret, and self-criticism are performed when reflecting on past humor. Furthermore, the paper highlights how humor accused of racism is more difficult to discuss than humor criticized for sexism or homophobia. The article contributes to an understanding of how anti-racist subject positions are constructed through retrospective reflections on old jokes—and what this reveals about discussions on humor, race, and racism in contemporary Sweden.